Chemical-dynamic polishing of InAs, InSb, GaAs and GaSb crystals with (NH₄)₂Cr₂O₇-HBr-citric acid etching composition - Levchenko, I.V.; Tomashyk, V.M.; Stratiychuk, I.B.; Malanych, G.P.; Stanetska, A.S.; Korchovyi, A.A. (Functional Materials, 2018)
The chemical dissolution of InAs, InSb, GaAs and GaSb crystals in (NH₄)₂Cr₂O₇-HBr-C₆H₈O₇ etching solutions has been investigated. The dissolution rate of the semiconductor materials has been measured as a function of etchant composition, stirring rate and temperature. The limiting stages of dissolution process, regions of the polishing and unpolishing solutions have been established. The polishing etchant compositions and conditions for chemical-dynamic polishing of the InAs, InSb, GaAs and GaSb crystals have been proposed and optimized.